Is Capability to Manage Finances Stable Over Time? - Lazar, Christina M. (Am J Psychiatr Rehabil, 2018)
Procedures to determine when people receiving disability payments are incapable of managing their money recently have been re-examined by the Social Security Administration. Understanding the time-course of financial capability is necessary because people who are judged capable of managing their funds at one point may go on to need supports in the future, and those judged incapable and assigned a fiduciary will need re-evaluation so they have the most possible autonomy over their funds management. The financial capability of 132 individuals was examined during acute treatment and twenty-four weeks later. The extent to which baseline variables predicted future capability were examined. More participants were assessed as financially incapable at baseline (n=72) than at the twenty-four-week follow-up (n=43). Most participants had stable capability across assessment periods (n=35 remained incapable; n=52 remained capable), however a substantial minority (n=37) moved from incapable to capable. People who transitioned from incapable to capable had greater net reductions in psychiatric distress ratings and days of alcohol use from baseline to follow-up, compared to people who remained incapable. In multivariate analyses, incapability at follow-up was predicted by having been rated incapable at baseline, drug use at baseline, and having a psychotic disorder. The high baseline rate of incapability determinations suggests that admission into intensive psychiatric programs may be a good time to assess an individual’s financial capability. However, these findings also suggest the importance of periodically reassessing beneficiaries’ capability because high proportions rated incapable were rated to be capable twenty-four weeks later.